1989
DOI: 10.1071/wr9890195
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Warfarin-Poisoning Campaign Against Feral Pigs, Sus Scrofa, in Namadgi National Park, A.c.t.

Abstract: The aim of this study was to develop better techniques for controlling feral pigs, Sus scrofa, in the event of an outbreak of an exotic disease than the use of 1080. Trail-baiting with warfarin-treated wheat killed 30 of 32 feral pigs carrying radio transmitters in Namadgi National Park, A.C.T., in May 1986. The casualties took 9.7 � 0.4 (mean � s.e.) days to die (range 6-14) and all died within 2.06 km of the bait trail. The two survivors (both males) were radio-located within 339 m of the poison trails sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 7 publications
2
26
1
Order By: Relevance
“…This method has been used in several feral pig poison-baiting studies in the past (McIlroy et al 1989;Saunders et al 1990). In Namadgi National Park, the population decline recorded using radio-transmitters was 94% and was identical to the decline recorded by extensive dung counts (McIlroy et al 1989;Hone 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has been used in several feral pig poison-baiting studies in the past (McIlroy et al 1989;Saunders et al 1990). In Namadgi National Park, the population decline recorded using radio-transmitters was 94% and was identical to the decline recorded by extensive dung counts (McIlroy et al 1989;Hone 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used in several feral pig poison-baiting studies in the past (McIlroy et al 1989;Saunders et al 1990). In Namadgi National Park, the population decline recorded using radio-transmitters was 94% and was identical to the decline recorded by extensive dung counts (McIlroy et al 1989;Hone 2002). Saunders et al (1990) reported a population decline using radio-transmitters of 86% following baiting using fermented grain dosed with warfarin, and speculated that this would have increased to 100% with time since the one surviving feral pig had consumed warfarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with hunting, live-trapping, and habitat management, control of both wild boar and feral pigs may be achieved through baiting with baits containing poison (McIlroy et al 1989;Saunders et al 1990;Cowled et al 2006;Twigg et al 2007) or contraceptives (Linhart et al 1997). Baiting with oral vaccines is also used for wildlife disease control (Baer 1976;Cross et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Control strategies should focus on all segments of wild pig populations, including boars, because they range over long distances (McIlroy et al 1989;Stevens 2010). Knowledge about the pathogens that reside in wild pig populations, how pigs traverse the landscape, and how each pathogen is transmissible will allow spatial prioritization of risk zones to facilitate strategic control efforts.…”
mentioning
confidence: 99%